Rates and Predictors of Professional Interpreting Provision for Patients With Limited English Proficiency in the Emergency Department and Inpatient Ward - Jennifer Ryan M.Ed; Samantha Abbato PhD, MPH; Ristan Greer PhD; Petra Vayne-Bossert MD; Phillip Good MBBS, PhD (SAGE Publishing, 2017)
The provision of professional interpreting services in the hospital setting decreases communication errors of clinical significance and improves clinical outcomes. A retrospective audit was conducted at a tertiary referral adult hospital in Brisbane, Australia. Of 20 563 admissions of patients presenting to the hospital emergency department (ED) and admitted to a ward during 2013-2014, 582 (2.8%) were identified as requiring interpreting services. In all, 19.8% of admissions were provided professional interpreting services in the ED, and 26.1% were provided on the ward. Patients were more likely to receive interpreting services in the ED if they were younger, spoke an Asian language, or used sign language. On the wards, using sign language was associated with 3 times odds of being provided an interpreter compared with other languages spoken. Characteristics of patients including their age and type of language spoken influence the clinician's decision to engage a professional interpreter in both the ED and inpatient ward.